Propensity Score Matched Analysis of Functional Outcomes Post Mechanical Thrombectomy of the Anterior Circulation Alone or Combined with Preoperative Intravenous Thrombolysis. (16th November 2020) - Salehani, Arsalaan; Elsayed, Galal; Chagoya, Gustavo; Self, D. Mitchell; Bernstock, Joshua; Ilyas, Adeel; Pope, Brandon; Gonzalez-Sigler, Irina; Segarra, Daniel; Stetler, William R; Harrigan, Mark R
Abstract: INTRODUCTION: Now the standard of care, endovascular therapy (EVT) has been shown to have an additive benefit to intravenous (IV) thrombolytics, e.g. tissue plasminogen activator (tPA), for patients with acute ischemic stroke (AIS) secondary to large vessel occlusions. IV tPA can restore blood flow in AIS, achieving recanalization when given in a time-dependent manner as a standalone therapy. However, IV tPA is not a benign treatment. It has been shown that IV tPA prior to EVT leads to increased rates of intracranial hemorrhage (ICH) and can limit the neurointerventionalist's repertoire of medications in the perioperative period. METHODS: A retrospective cohort study was performed with 168 patients analyzed and 110 patients suitably matched with propensity scores. Parametric statistics were utilized for tests of heterogeneity and propensity score adjusted multivariate logistic regression compared mRS 0–2 versus 3–5 controlling for gender, smoking, atrial fibrillation, diabetes, hypertension, hyperlipidemia, the use of preoperative intravenous thrombolytics and mRS on admission. RESULTS: Of the 168 patients analyzed, 85 received IV tPA prior to their thrombectomy. Administration of IV tPA was significantly associated with worse 90day mRS ( P = . 002; mRS 3–5 OR = 4.18, CI 3.41-4.94). Diabetes also led to higher odds of mRS 3–5 at 90 days (OR = 3.36, CI 2.31-4.42). Use of IV tPA did not significantly affect length of procedure or stay, discharge disposition or death. A propensity score matched dataset showed a 90day mRS 3–5 odds ratio of 5.22 (CI 4.33 - 6.11, p-value 0.0002) in the IV tPA group. CONCLUSION: The use of IV tPA with mechanical thrombectomy results in greater odds of 90day mRS 3–5 without increased mortality. Therefore, patients and their families must be sufficiently counseled regarding the risk of severe morbidity with IV tPA use. Propensity score matching could not be applied to NIHSS or general anesthesia without losing effective study power due to small sample size.